Consideration on hemicraniectomy - Horatiu Stan (Romanian Neurosurgery, 2009)
Decompressive hemicraniectomy is a surgical technique used to relieve the increased intracranial pressure. There is no standardized surgical technique to clearly state the minimum area of the cranial vault needed to obtain the best results. The aim of the current paper is to present our surgical technique and experience used in performing hemicraniectomies, technique that we consider optimal for his purpose. Our experience consists in 17 operated cases and eleven patients (64.7%) were long term survivors.